Congenital fistulae of the lower lip in Van der Woude syndrome: A histomorphological study - Onofre, Mirian Aparecida [UNESP]; Brosco, H. B.; Brosco, J. U.; Taga, R. (Amer Cleft Palate-craniofacial Assoc, 1999)
Objective: To evaluate a significant number of cases of fistulae of the lower lip with the light microscope in order to investigate the histological variation and to attempt to define the histopathological pattern of the lesion.Methods: Congenital fistulae of the lower lips of 17 patients with Van der Woude syndrome were analyzed by light microscopy,Results and Conclusion: the walls of most of the fistulae consisted of stratified nonkeratinized squamous epithelium and a lamina propria of dense connective tissue with areas of lymphohistiocytic inflammatory infiltrates. Bundles of striated muscle fibers, blood vessels, nerves, adipose tissue, and mixed acinar glands were observed. These glands surrounded the entire wall of the lesion, and their excretory ducts opened into the lumen of the fistula, explaining the clinical observation of elimination of mucous secretion through the opening of the fistula, Two microform cases of fistula were analyzed that presented only a depression in the epithelium at the site corresponding to the opening of the fistula.
Keywords: congenital fistulae of lower lip; morphology; Van der Woude syndrome